Analisis kemampuan pemecahan masalah siswa smp kelas IX dalam menyelesaikan soal matematika tipe Higher Order Thinking Skill (HOTS) - Tiara Fikriani; Mirda Swetherly Nurva (AKSIOMA : Jurnal Matematika dan Pendidikan Matematika, 2020)
High Order Thinking Skill or HOTS should be had by the students to improve students thinking skills at a higher level are continued in curriculum 2013. The purpose of this study to determine the ability to solve student problems in working on the problem type Higher Order Thinkimg Skills (HOTS). By working on the Higher Order Thinking Skills questions, students will reach the levels of mathematical ability from the lowest level to the highest level. The type of this research is qualitative research with natural setting. Data collection using observation, test, and interview methods. The results of this study obtained the conclusion that students in solving problems using Polya step, can meet the indicators analyze, create, and evaluate.